2020
DOI: 10.1002/vms3.338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N‐Acetylcysteine on the reproductive performance, oxidative stress and RNA sequencing of Nubian goats

Abstract: N‐acetylcysteine (NAC) has been found to enhance the protective ability of cells to counter balance oxidative stress and inflammation. To investigate the effects of dietary NAC supplementation on the reproductive performance of goats, the reproductive performance and endometrial transcriptome of goats fed with diets with NAC (NAC group) and without NAC supplementation (control group) were compared. Results showed that the goats fed with 0.03% and 0.05% NAC had similar litter size, birth weight, nitric oxide (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Our preliminary data suggest that NAC can increase the conception rate of Qianbei Ma goats. In a previous study with Nubian goats, we found that NAC significantly increases the litter size [ 22 ]. However, our available data suggest that NAC can increase the litter size of Qianbei Ma goats, but the increase is not significant.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our preliminary data suggest that NAC can increase the conception rate of Qianbei Ma goats. In a previous study with Nubian goats, we found that NAC significantly increases the litter size [ 22 ]. However, our available data suggest that NAC can increase the litter size of Qianbei Ma goats, but the increase is not significant.…”
Section: Discussionmentioning
confidence: 98%
“…The number of embryos in the euthanized goats was recorded. To ensure consistency with previous work, the experimental goats were fed a previously described basal diet [ 22 ]. Specific information is provided in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protective effect elicited by NAC is due to NAC antioxidant capacity replenishing cellular glutathione stores and modulation of intracellular molecular signalling pathways involved in inflammatory responses. Evidence in the literature suggests that NAC anti‐inflammatory roles are incumbent on inhibiting pro‐inflammatory cytokine synthesis (Jarazo Dietrich et al., 2015; Luo et al., 2020; Wang, Guo, et al., 2020; Zheng et al., 2019) and suppression of the NF‐kB signalling pathways (Guo et al., 2018). Besides, via several molecular pathways, NAC balances tissue redox homeostasis and averts oxidative stress (Colasuonno et al., 2020; Ghafarizadeh et al., 2020; Kazaz et al., 2019; Navaratnarajah et al., 2020; Turkmen et al., 2019) that can cause cell membrane damage and impact sperm integrity and function.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of NAC mitigated the effect of PFOA in reducing the serum concentration of reproductive hormones. Figure 10 depicts the plausible mechanistic pathway by which NAC abates the Dietrich et al, 2015;Luo et al, 2020;Wang, Guo, et al, 2020;Zheng et al, 2019) and suppression of the NF-kB signalling pathways (Guo et al, 2018). Besides, via several molecular pathways, NAC balances tissue redox homeostasis and averts oxidative stress (Colasuonno et al, 2020;Ghafarizadeh et al, 2020;Kazaz et al, 2019;Navaratnarajah et al, 2020;Turkmen et al, 2019) that can cause cell membrane damage and impact sperm integrity and function.…”
Section: Discussionmentioning
confidence: 99%